Good thinking : seven powerful ideas that influence the way we think - Cummins, Denise D. (Cambridge : Cambridge University Press, 2021)
This book is for anyone who wonders whether to trust the media, seeks creative solutions to problems, or grapples with ethical dilemmas. Cognitive scientist Denise D. Cummins clearly explains how experts in economics, philosophy, and science use seven powerful decision-making methods to tackle these challenges. These techniques include: logic, moral judgment, analogical reasoning, scientific reasoning, rational choice, game theory and creative problem solving. Updated and revised in a second edition, each chapter now features quizzes for course use or self-study.
Title from publisher's bibliographic system (viewed on 04 Mar 2021).
Keywords: Thought and thinking; Game theory; Rational choice theory